2014
DOI: 10.1007/s12311-014-0610-3
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Paper: Radiological Biomarkers of Cerebellar Diseases

Abstract: Hereditary and sporadic cerebellar ataxias represent a vast and still growing group of diseases whose diagnosis and differentiation cannot only rely on clinical evaluation. Brain imaging including magnetic resonance (MR) and nuclear medicine techniques allows for characterization of structural and functional abnormalities underlying symptomatic ataxias. These methods thus constitute a potential source of radiological biomarkers, which could be used to identify these diseases and differentiate subgroups of them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 168 publications
(245 reference statements)
1
39
0
Order By: Relevance
“…Additionally, the left putamen had increased RSFC with the vermis in SUIC patients. While studies of cerebellar disease have shown the vermis and putamen are both a part of motor circuitry , this finding may also implicate them in a cognitive/emotion regulation role. This is supported by structural neuroimaging research, which has found the vermis to be associated with several affective disorders .…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, the left putamen had increased RSFC with the vermis in SUIC patients. While studies of cerebellar disease have shown the vermis and putamen are both a part of motor circuitry , this finding may also implicate them in a cognitive/emotion regulation role. This is supported by structural neuroimaging research, which has found the vermis to be associated with several affective disorders .…”
Section: Discussionmentioning
confidence: 91%
“…3 Imaging biomarkers of disease progression are desirable in view of future trials in inherited ataxias. 4 MRI has previously demonstrated brain damage in FRDA in form of regional atrophy of the medulla, peridentate cerebellar white matter (WM) and superior cerebellar peduncles in T1-weighted imaging [5][6][7][8][9] and of change of microstructural diffusion-related characteristics of WM tracts of the brainstem, cerebellar peduncles, cerebellum and supratentorial structures in diffusion-weighted, or diffusion tensor imaging (DTI). [10][11][12][13][14][15] Regional atrophy and microstructural diffusion-related changes were however, seen to correlate with disease duration and severity of clinical deficit in several crosssectional studies.…”
Section: Introductionmentioning
confidence: 99%
“…Oculomotor disturbances are a common and often early sign in most hereditary ataxias. Specific oculomotor abnormalities, such as saccade slowing, are helpful in the diagnosis of hereditary atxias . Presence or absence of oculomotor signs is recorded by the INAS together with nonataxia signs.…”
Section: Methodsmentioning
confidence: 99%
“…Specific oculomotor abnormalities, such as saccade slowing, are helpful in the diagnosis of hereditary atxias. 56 Presence or absence of oculomotor signs is recorded by the INAS together with nonataxia signs. Quantitative recording of eye movements has been performed in several monocentre studies.…”
Section: Eye Movement Trackingmentioning
confidence: 99%